2013
DOI: 10.1080/14786435.2013.843795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of loading parameters on single-crystal slip in tantalum using molecular mechanics

Abstract: This study is aimed at developing a physics-based crystal plasticity finite element model for body-centred cubic (BCC) metals, through the introduction of atomiclevel deformation information from molecular dynamics (MD) investigations of dislocation motion at the onset of plastic flow. In this study, three critical variables governing crystal plasticity mediated by dislocation motion are considered. MD simulations are first performed across a range of finite temperatures up to 600K to quantify the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…at very low temperature (77 K), which are close to those identified in atomistic simulations for tantalum (Alleman et al, 2014). However, they were further tuned to capture the yield stresses at 77 K. f Figure 6a the stress-strain curves with the Schmid law were presented together (dashed lines for both compression and tension); the symmetric yield stress predicted with the Schmid law was apparently located between the yield stresses for compression and tension with non-Schmid effects.…”
Section:  supporting
confidence: 63%
“…at very low temperature (77 K), which are close to those identified in atomistic simulations for tantalum (Alleman et al, 2014). However, they were further tuned to capture the yield stresses at 77 K. f Figure 6a the stress-strain curves with the Schmid law were presented together (dashed lines for both compression and tension); the symmetric yield stress predicted with the Schmid law was apparently located between the yield stresses for compression and tension with non-Schmid effects.…”
Section:  supporting
confidence: 63%
“…On studying the extensive literature on the list of potential energy functions for Ta, the angular dependent potential function of Mishin et al [28] has been reported to agree well with the ab-initio calculations while the analytical Embedded-atommethod (EAM) potential proposed by Guellil et al [29] shows 27% discrepancy between the calculated and experimental values of bulk modulus [30] of Ta. Smith et al [15] noted that the EAM potential by Li et al [30] has been rigorously researched by Alleman et al [31], who find this potential function being robust in revealing elastic modulus, predictions of gamma surfaces, BCC screw dislocation core and unstable stacking fault energy barrier determined by density functional theory (DFT) calculations. However, a comparison across several potential functions [32] specifically compared to study the nanoindentation process suggests that the potential energy function proposed by Li et al [30] poses some serious concerns on the simulation results and is hence unreliable to study Ta under the conditions of high pressure.…”
Section: Molecular Dynamics Simulation Of Nanoindentationmentioning
confidence: 99%
“…Based on these findings, a yield criterion was developed in (Gröger et al, 2008b) to include three non-Schmid terms: shear stress on the nearest secondary ሼ112ሽ slip plane to a given primary ሼ110ሽ slip plane in the twinning or the anti-twinning direction, and shear stresses in the primary ሼ110ሽ and the secondary ሼ112ሽ slip planes perpendicular to their respective slip directions. The criterion was later incorporated in single crystal plasticity models (Alleman et al, 2014;Weinberger et al, 2012). The other yield criterion developed in (Dao and Asaro, 1993;Lim et al, 2013) is more general and includes the applied shear and normal stresses along all three orthogonal axis on a given slip plane.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that slip on ሼ123ሽ planes can be expressed as a combination of slips on ሼ110ሽ, and ሼ112ሽ planes (Franciosi, 1983;Franciosi, 1985). Therefore, more often models assume slip on the ሼ110ሽ and ሼ112ሽ slip planes (Alleman et al, 2014;Ardeljan et al, 2014;Ito and Vitek, 2001;Knezevic et al, 2013b;Ma et al, 2007;Wang and Beyerlein, 2011), and sometimes only on the ሼ110ሽ slip plane (Gröger et al, 2008b;Lim et al, 2013;Weinberger et al, 2012). The uncertainty in the identification of active slip systems poses a fundamental problem for simulating texture evolution and mechanical response because the difference in relative activities of slip systems results in a difference in texture evolution.…”
Section: Introductionmentioning
confidence: 99%